Kesesuaian Materi Terhadap Kompetensi Inti dan Kompetensi Dasar pada Buku Ajar Bahasa Arab - Handayani, Rina Asih (LISANIA: Journal of Arabic Education and Literature, 2018)
This study aims to reveal material conformity to core competencies and basic competencies in Arabic textbooks. In this research, the author uses library research method.Â  The data collection used is documentation techniques, and then the data are analyzed by using content analysis. The result of this research shows that from the three components of conformity assessment of textbook materials with Core Competence and Basic Competence, the material completeness component obtained is 57% (3 = complete enough), the second component about the material breadth is obtained by the result of 62% (3 = wide enough), and in the third component about the material depth, the percentage value is 85% (5 = very deep). Furthermore, from the three results of the analysis, it is obtained the average value of percentage of 68%, which means that the conformity of Arabic textbooks for VII grade published by the Ministry of Religious Affairs is with Core Competence and Basic Competence of 68% or in the category of quite appropriate (3). With this result, Arabic textbooks for VII grade published by the Ministry of Religious Affairs can be used as a compulsory handbook for students.